Naturalized epistemology and philosophy of science - Mi, Chienkuo, 1962-; Chen, Ruey-lin. (Rodopi Philosophical Studies, 2007)
Much has happened in the field of contemporary epistemology since Quine's "Epistemology Naturalized" was published in 1969. Even before Ronald Giere published his article "Philosophy of Science Naturalized," naturalized philosophy of science had been influenced by the so-called historical approach. Kuhm, Lakatos, Feyerabend and Laudan all contributed importantly to this trend. In this light it has emerged, without a doubt, that philosophy of science is closely related to epistemology. This volume explores some of the relevant relations and will be of interest to epistemologists and philosophers of science.